1981
DOI: 10.1001/archotol.1981.00790450034011
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiopericytoma of the Tracheal Wall

Abstract: hemangiopericytoma occurred on the posterior tracheal wall in a 46-year-old man. A review of the pathologic findings showed that compressed groups of capillaries were lined by an intact reticulin sheath that was surrounded by spindleshaped pericytes. The ultramicroscopic findings of small spindle cells with a surrounding basal lamina and intracellular microfilaments in the absence of neurosecretory granules are important diagnostic features. Emphasis is placed on the impossibility of differentiating benign and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Malignant lesions of the trachea are rare tumours, and among them hemangiopericytomas are exceptional. To our knowledge there have been only three other cases of a hemangiopericytoma occurring in the trachea (Alvarez-Vicent, 1969;Bremond et al, 1975;Ballard and Yarington, 1981). The case reported by Bremond et al (1975) and our own case showed a very similar behaviour, much more aggressive than the cases mentioned by Alvarez-Vicent (1969) and Ballard and Yarington (1981).…”
Section: Commentsupporting
confidence: 65%
See 2 more Smart Citations
“…Malignant lesions of the trachea are rare tumours, and among them hemangiopericytomas are exceptional. To our knowledge there have been only three other cases of a hemangiopericytoma occurring in the trachea (Alvarez-Vicent, 1969;Bremond et al, 1975;Ballard and Yarington, 1981). The case reported by Bremond et al (1975) and our own case showed a very similar behaviour, much more aggressive than the cases mentioned by Alvarez-Vicent (1969) and Ballard and Yarington (1981).…”
Section: Commentsupporting
confidence: 65%
“…Since the report in 1762 of a tracheal tumour by Morgagni (Morgagrii, 1769) there have been fewer than 400 cases of tracheal cancers reported in the literature, most of them (60 per cent) arising from the posterior and lateral walls of the trachea (Houston et al, 1969). Only three of these tumours were hemangiopericytomas (Alvarez-Vicent, 1969;Bremond et al, 1975;Ballard and Yarington, 1981), two of them confirmed by electron microscopic study (Bremond et al, 1975;Ballard and Yarington, 1981).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Among the benign mesenchymal tumours the reported entities have included fibromas (Gilbert et al, 1953;MacLachlan, 1968), fibromyxoma (Pollak et al, 1985), fibrous histiocytoma (Sandstorm et al, 1978), granular cell tumour (Mikaelian etal., 1984), leiomyoma (Harris et al, 1967), and neurilemmoma (Horovitz etal., 1983). Paraganglioma (Liew etal., 1981), haemangiopericytoma (Ballard and Yarington, 1981) and hamartoma (Engelking, 1959) are also exceedingly rare lesions. One case of plasma cell granuloma (Satomi et al, 1991) has been reported recently in the subglottic region of a 55-year-old woman and perhaps is closely related to the present case.…”
Section: Discussionmentioning
confidence: 99%